Best supportive care for idiopathic pulmonary fibrosis: current gaps and future directions - Ferrara, Giovanni; Luppi, Fabrizio; Birring, Surinder S.; Cerri, Stefania; Caminati, Antonella; Sköld, Magnus; Kreuter, Michael (European respiratory review, 2018)
Best supportive care (BSC) is generally defined as all the interventions and the multiprofessional approach aimed to improve and optimise quality of life (QoL) in patients affected by progressive diseases. In this sense, it excludes and might be complementary to other interventions directly targeting the disease. BSC improves survival in patients with different types of cancer. Patients with idiopathic pulmonary fibrosis (IPF) experience a vast range of symptoms during the natural history of the disease and might have a beneficial effect of BSC interventions. This review highlights the current evidence on interventions targeting QoL and gaps for the clinical assessment of BSC in the treatment of IPF patients. Very few interventions to improve QoL or improve symptom control are currently supported by well-designed studies. Sound methodology is paramount in evaluating BSC in IPF, as well as the use of validated tools to measure QoL and symptom control in this specific group of patients.
Gesehen am 18.05.2020